Analisis Pemanfaatan Artificial Intelligence untuk Meningkatkan Efisiensi dalam Proses Penyusunan Laporan Keuangan - Al Fatya, Kayyana Ihsan; Endah Susilowati (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
The rapid advancement of technology has driven transformation across various sectors, including the field of accounting. The utilization of Artificial Intelligence (AI) in accounting significantly enhances the efficiency of financial statement preparation through process automation, reduction of human errors, and the ability to process large-scale data quickly and accurately. This study aims to analyze the role and impact of AI in the preparation of financial statements, as well as to identify the benefits and challenges associated with its implementation. The research employs a literature review approach combined with the author’s empirical experience. The results indicate that the use of AI in accounting has a positive impact on the efficiency and effectiveness of accountants’ work, especially in the financial reporting process. Despite its numerous advantages, the implementation of AI still faces challenges such as limited human resource capabilities, the need for ongoing technological training, and the protection of sensitive financial data.